(untitled) (Research, Society and Development, 2022)
Bats are reservoirs of a diversity of viruses. Among the viruses recorded in bats, retroviruses are among the most significant virus families because they cause persistent infection in the animals. Recent reports of retroviruses circulating in bat populations have identified several retroviruses from other animals in these mammals. We aimed from viral Metagenomics, to identify retroviral sequences of interest in Veterinary Medicine, in Amazonian urban bat species. Using Next Generation Sequencing (SNG) on Illumina Platform and based on BLAST (Basic Local Alignment Search Tool), we analyzed 168 samples (56 from blood, 56 from oral swab and 56 from anal swab) from 56 bats of the species Noctilio albiventris (n=18), N. leporinus (n=1), Artibeus lituratus (n=13), Myotis sp. (n=6) and Molossus molossus (n=18). As a result, we observed that four genera of retroviruses had readings, these being: Alpharetrovirus, Betaretrovirus, Gammaretrovirus and Lentivirus. The oral swab pools had more number of viral contigs identified by similarity in BLAST. The total retroviral sequences were: Duck infectious anemia virus, Feline leukemia virus, Gibbon ape leukemia virus, Avian leukosis virus, Reticuloendotheliosis virus, Feline mmunodeficiency virus, Mason Pfizer monkey virus, Enzootic nasal tumour virus of goat e Simian retrovirus Y. We show from our metagenomic analysis, that there is circulation of retroviruses from other reservoirs, such as felines, sheep and birds, in the chyropterofauna of the region and report such records in order to warn about permanent surveillance of bats for new retroviruses and investigations of biological characteristics and infectious potential of such viruses.